Emotional Intelligence and Work Performance at the K-Link K-Link Sidoarjo Branch Multi-Level Marketing (MLM) Distributor - Ririn Dewanti Dian Samudera Indriani; Merah Purnama Sari (Psikologia : Jurnal Psikologi, 2015)
Employee performance is very influential to the success of a company, especially a company based in the field of multi-level marketing (MLM) in which a person in demand hard to be able to use their emotional intelligence in order to get satisfactory results for their customers. The purpose of this study to determine the relationship of emotional intelligence with performance on the distributor of multi level marketing (MLM). This study used a quantitative approach. The variables of this study was emotional intelligence as an independent variable (X) and the interpretation of the work as the dependent variable (Y). The Sampling techniques was 100distributors through proposive sampling based on predetermined criteria. Process analysis using Pearson product moment correlation analysis performed using SPSS-17 For Windouws. Results of correlation (Pearson correlation) obtained = 0689 and p <0.05 (0.000 <0.05), which means that there was a relationship of emotional intelligence with work performance distributors of Multi Level Marketing.